To snack or not to snack: Using fNIRS to link inhibitory control to functional connectivity in the toddler brain. Issue 4 (17th January 2022) - Kerr‐German, Anastasia; Namuth, August; Santosa, Hendrik; Buss, Aaron T.; White, Stuart
Abstract: Inhibitory control (IC) emerges in infancy, continues to develop throughout childhood and is linked to later life outcomes such as school achievement, prosocial behavior, and psychopathology. Little, however, is known about the neural processes underpinning IC, especially in 2‐year‐olds. In this study, we examine functional connectivity (FC) in 2.5‐year‐olds while recording hemodynamic responses via functional infrared spectroscopy (fNIRS) during a traditional snack delay task. We found that functional connectivity strength between left frontal and parietal cortex and bilateral parietal cortex were positively associated with performance on this task. The current findings present the first neural data for toddlers during this IC task. Further, these data are the first to link this self‐regulatory process to differences in brain development within this population. Implications for future directions and work with clinical populations are discussed.